Dose‐dependent collagen cross‐linking of rabbit scleral tissue by blue light and riboflavin treatment probed by dynamic shear rheology. (16th December 2014) - Schuldt, Carsten; Karl, Anett; Körber, Nicole; Koch, Christian; Liu, Qing; Fritsch, Anatol W.; Reichenbach, Andreas; Wiedemann, Peter; Käs, Josef A.; Francke, Mike; Iseli, Hans Peter
Abstract Purpose To determine the visco‐elastic properties of isolated rabbit scleral tissue and dose‐dependent biomechanical and morphological changes after collagen cross‐linking by riboflavin/blue light treatment. Material Scleral patches from 87 adult albino rabbit eyes were examined by dynamic shear rheology. Scleral patches were treated by riboflavin and different intensities of blue light (450 nm), and the impact on the visco‐elastic properties was determined by various rheological test regimes. The relative elastic modulus was calculated from non‐treated and corresponding treated scleral patches, and treatments with different blue light intensities were compared. Results Shear rheology enables us to study the material properties of scleral tissue within physiological relevant parameters. Cross‐linking treatment increased the viscous as well as the elastic modulus and changed the ratio of the elastic versus viscous proportion in scleral tissue. Constant riboflavin application combined with different blue light intensities from 12 mW/cm2 up to 100 mW/cm2 increased the relative elastic modulus of scleral tissue by factors up to 1.8. Further enhancement of the applied light intensity caused a decline of the relative elastic modulus. This might be due to destructive changes of the collagen bundle structure at larger light intensities, as observed by histological examination. Conclusion Collagen cross‐linking by riboflavin/blue light application increases the biomechanical stiffness of the sclera in a dose‐dependent manner up to certain light intensities. Therefore, this treatment might be a suitable therapeutic approach to stabilize the biomechanical properties of scleral tissue in cases of pathological eye expansion.